DNA replication with an unnaturally large replicon in Saccharomyces cerevisiae - Wallis, A (2019)
Eukaryotic cells co-regulate DNA replication and the cell cycle, ensuring a single round of replication occurs during each cell cycle. Until a few years ago, origin licensing and subsequent activation was considered to be a stepwise activation process, dependent on cell cycle kinases. However, it is now known that some phosphatases also play a key role in regulating DNA replication. A potential role during DNA replication initiation for the phosphatase subunit Rts1 was examined. Temperature-sensitive replication initiation mutants were examined to determine if synthetic rescue resulted when RTS1 was deleted (indicating antagonistic functions). It was shown that Rts1 did not antagonise origin licensing or activation. Conversely, RTS1 was found to have negative genetic interactions with CDC9, DBP11 and CDC45. Re-initiation of replication origins (re-replication) has been associated with tumorigenesis; however, the opposite phenomenon (under-replication) has been less well studied. Potential outcomes include single-stranded DNA protection, alternative replication mechanisms, chromosome breaks, ‘fragile sites’ and/or cell death. This project aimed to create a system containing an unnaturally large replicon of over 100 kb, and characterise the resulting effects on cell growth and DNA replication. DNA replication was delayed in the absence of adjacent active origins. However, mean generation time was not always extended. A next-generation sequencing approach, utilised to examine replication fork direction, indicated that replication forks could initiate close to telomeres despite origin inactivations, termed telomeric initiation.